Evaluation of Blended Learning in Nursing Education at the Kurdistan Region in Iraq - Murtadha Younes Mohammed, Mohammed F. Khalifa (Pakistan Journal of Medical & Health Sciences, 2022)
Objective(s): To evaluate blended learning in nursing education at the Kurdistan Region in Iraq. Design: A descriptive study, using evaluation approach, is conducted to evaluate blended learning in nursing education in Iraq from September 26th, 2021 to March 22nd, 2022.The study is carried out at three Colleges of Nursing at the University of Duhok, University of Sulaymania and Hawler Medical University. A convenient, non-probability, sample of (90) undergraduate nursing students is selected. The sample is comprised of (30) student from each college of nursing, Self-report questionnaire is constructed from the literature, for evaluating the blended learning in nursing education at these colleges of nursing. The instrument consists of two parts which they include students’ socio-demographic data and evaluation of blended learning in nursing education. A pilot study is conducted for the determination of the study instrument’s content validity and internal consistency reliability. Results: The findings indicate that Colleges of Nursing at the Kurdistan Region in Iraq have experienced fair performance of blended learning relative to its domains in nursing education. Conclusion: It is discovered, in the present study, that the blended learning program application is not influenced by learners’ demographic characteristics of age, gender, grade, family monthly income and residency. Recommendations: The study recommends that the implementation blended learning in nursing education should be seriously monitored for the benefits of the colleges of nursing, instructors and learners, supportive alternatives should be presented to both of the instructors and learners.